The Slametan Tradition of Seven Months Pregnancy (Mitoni) in Kedunggalar Ngawi - Alpi Ahyuni; Ida Hamidah; Anik Khoridah (Javanologi: International Journal of Javanese Studies, 2023)
Abstract This study aims to reveal the characteristics and also the process of mitoni tradition in Javanese society, especially in Kedunggalar Ngawi East Java as radisi that is still preserved and practiced today. The method used in this study is qualitative descriptive. Data collection was carried out by observation, interviews and documentation on the practice of mitoni tradition in Kedunggalar Ngawi, while data analysis was carried out descriptively. The tradition of slametan seven months of pregnancy (mitoni, tingkeban) developed with the tide of social, cultural, and religious change, but the change did not stray far from its roots. This study is expected to provide insight into the culture or tradition of mitoni in the Kedunggalar Ngawi area. This research also intends to review and revive the mitoni tradition that still exists and is practiced by the Kedunggalar community in the midst of modernization. In essence, the implementation of the mitoni tradition is a prayer request for the conceived baby and the future mother to get protection from Allah Swt. The tradition of slametan seven months of pregnancy (mitoni) is carried out by the community as gratitude to Allah Swt for all the blessings that have been given and kept away from everything unwanted and disaster.Keywords: Tradition, Slametan, Mitoni, Tingkeban